Peningkatan Kapasitas Masyarakat Dalam Deteksi Dini Kanker Serviks Melalui Edukasi Iva Berbasis Klinik Di Klinik Romana, Desa Tanjung Anom - Jamila; Henna Mei Magdalena Purba; Maris Sembiring (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Cervical cancer is one of the leading causes of death among women in Indonesia, yet it is preventable through early detection such as VIA (Visual Inspection with Acetic Acid). Low health literacy and limited access to education remain key challenges in rural areas, including Tanjung Anom Village. This community service aimed to increase knowledge and participation of women of reproductive age in VIA screening through a clinic-based educational approach at Romana Clinic. A participatory method was applied by involving local communities, health cadres, and medical personnel. The results showed a significant increase in participants’ knowledge scores from an average of 54.6 to 78.9 after the training. A total of 39 women underwent VIA screening, and a women’s education group was established to ensure program sustainability. This activity also led to the emergence of local leadership and collective awareness as early signs of social transformation. The clinic-based education model has proven to be effective and suitable for replication in other rural settings.